The significance of performing the OPGs in the detection of dentigerous cyst and mesiodentes - a case report - Białkowska-Głowacka, Jolanta; Pińkowska-Prasał, Małgorzata; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes a case of a maxillary dentigerous cyst with mesiodens in a 60-year-old patient, which was discovered accidentally on an OPG.